2009
DOI: 10.1155/2009/579430
|View full text |Cite
|
Sign up to set email alerts
|

The SPES3 Experimental Facility Design for the IRIS Reactor Simulation

Abstract: IRIS is an advanced integral pressurized water reactor, developed by an international consortium led by Westinghouse. The licensing process requires the execution of integral and separate effect tests on a properly scaled reactor simulator for reactor concept, safety system verification, and code assessment. Within the framework of an Italian R&D program on Nuclear Fission, managed by ENEA and supported by the Ministry of Economic Development, the SPES3 facility is under design and will be built and operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 4 publications
(4 reference statements)
0
9
0
Order By: Relevance
“…Potential applications of the proposed anomaly detection method include real-time detection of component-level anomalies in nuclear power plants with low false alarm and missed detection rates. While the training stage could be accomplished in a nuclear power plant simulator with high fidelity (e.g., scaled experimental reactor [34] or computer simulator [35]), the testing stage should be ideally performed in real time in an operating nuclear power plant. However, based on the simulation results only, it is found that the plant perturbation needed to execute the proposed anomaly detection method require small induced changes in the turbine load (e.g., less than 2% nominal load) over a short period, which does not have any significant adverse effects on stability and performance of the plant operation.…”
Section: Summary Conclusion and Future Workmentioning
confidence: 99%
“…Potential applications of the proposed anomaly detection method include real-time detection of component-level anomalies in nuclear power plants with low false alarm and missed detection rates. While the training stage could be accomplished in a nuclear power plant simulator with high fidelity (e.g., scaled experimental reactor [34] or computer simulator [35]), the testing stage should be ideally performed in real time in an operating nuclear power plant. However, based on the simulation results only, it is found that the plant perturbation needed to execute the proposed anomaly detection method require small induced changes in the turbine load (e.g., less than 2% nominal load) over a short period, which does not have any significant adverse effects on stability and performance of the plant operation.…”
Section: Summary Conclusion and Future Workmentioning
confidence: 99%
“…The conceptual design and features of SPES3 IET facility are presented in Ref. [8]. The basic scaling criteria for designing SPES3 as a model for the IRIS prototype were:…”
Section: Introductionmentioning
confidence: 99%
“…The design of new nuclear reactors requires carrying out integral and separate effect tests on simulation facilities, as well as performing safety systems verification and safety code validation. Within the framework of an Italian R&D program on nuclear fission, managed by ENEA and supported by the Ministry of Economic Development, the SPES3 (pressurized simulator for safety experiments) experimental facility, described by Carelli et al [1], able to simulate the innovative small and medium size (PWR pressurized water reactor) nuclear reactors, is being built and will be operated at the SIET Company laboratories in Piacenza, Italy. In such facility, some design and beyond design basis accidents, like loss of coolant accidents (LOCAs), with and without the emergency heat removal systems, will be simulated [2].…”
Section: Introductionmentioning
confidence: 99%